Canopy gaps promote selective stem-cutting by small mammals of two dominant tree species in an African lowland forest: the importance of seedling chemistry. (7th October 2015) - Norghauer, Julian M.; Röder, Gregory; Glauser, Gaëtan
Abstract: Small mammals can impede tree regeneration by injuring seedlings and saplings in several ways. One fatal way is by severing their stems, but apparently this type of predation is not well-studied in tropical rain forest. Here, we report on the incidence of 'stem-cutting' to new, wild seedlings of two locally dominant, canopy tree species monitored in 40 paired forest understorey and gap-habitat areas in Korup, Cameroon following a 2007 masting event. In gap areas, which are required for the upward growth and sapling recruitment of both species, 137 seedlings of the long-lived, light-demanding, fast-growing large tropical tree ( Microberlinia bisulcata ) were highly susceptible to stem-cutting (83% of deaths) — it killed 39% of all seedlings over a c . 2-y period. In stark contrast, seedlings of the more shade-tolerant, slower-growing tree species ( Tetraberlinia bifoliolata ) were hardly attacked (4.3%). In the understorey, however, stem-cutting was virtually absent. Across the gap areas, the incidence of stem-cutting of M. bisulcata seedlings showed significant spatial variation that could not be explained significantly by either canopy openness or Janzen–Connell type effects (proximity and basal area of conspecific adult trees). To examine physical and chemical traits that might explain the species difference to being cut, bark and wood tissues were collected from a separate sample of seedlings in gaps (i.e. not monitored for stem-cutting). These analyses suggested that, compared with T. bifoliolata, the lower stem density, higher Mg and K and fatty acid concentrations in bark, and fewer phenolic and terpene compounds in M. bisulcata seedlings made them more palatable and attractive to small-mammal predators, likely rodents. We conclude that selective stem-cutting is a potent countervailing force to the current local canopy dominance of the grove-forming M. bisulcata by limiting the recruitment and abundance of its saplings. Given the ubiquity of gaps and ground-dwelling rodents in pantropical forests, it would be surprising if this form of lethal browsing was restricted to Korup.